تقويم كتاب الأحياء للصف السادس العلمي من وجهة نظر المدرسين والمدرسات استبانة استطلاعية لتقويم كتاب الاحياء للصف السادس العلمي من وجهة نظر المدرسين والمدرسات في مركز مدينة الموصل للعام الدراسي (2018 – 2019) (Journal of the College of Basic Education, 2022)
The current research aims at evaluating the biology book for sixth grade year, from the standpoint of teachers and identifies current research:biology Book for Scientific Grade, Sixth edition 2017. 2. A sample of teachers of both gender at the center of the city ofMosul for the academic year 2018-2019.The researcher used the questionnaire, which was developed afterreviewing the previous studies, A survey questionnaire was develop inits prelimin from and the teachers and educational specialists wereacquired with (21) paragraphs in the content of biology book for scientific sixth, and to be honest presented to group of experts andarbitrators, the research adopted (80%) indicators to accept or refusedparagraphs a questionnaire was found which included (21) paragraphs presented to the randomly selected sample of (30) teachersdistributed in (20) secondary schools, the researcher used thestatistical means Pearson correlation coefficient, the weight averageextraction unit paragraph and weight percentile.